Termites Are Associated with External Species-Specific Bacterial Communities - Soukup, Patrik; Větrovský, Tomáš; Stiblik, Petr; Votýpková, Kateřina; Chakraborty, Amrita; Sillam-Dussès, David; Kolařík, Miroslav; Odriozola, Iñaki; Lo, Nathan; Baldrian, Petr; Šobotník, Jan; Bourguignon, Thomas (Applied and environmental microbiology, 2021)
All termites have established a wide range of associations with symbiotic microbes in their guts. Some termite species are also associated with microbes that grow in their nests, but the prevalence of these associations remains largely unknown. Here, we studied the bacterial communities associated with the termites and galleries of three wood-feeding termite species by using 16S rRNA gene amplicon sequencing. We found that the compositions of bacterial communities among termite bodies, termite galleries, and control wood fragments devoid of termite activities differ in a species-specific manner. Termite galleries were enriched in bacterial operational taxonomic units (OTUs) belonging to Rhizobiales and Actinobacteria, which were often shared by several termite species. The abundance of several bacterial OTUs, such as Bacillus, Clostridium, Corynebacterium, and Staphylococcus, was reduced in termite galleries. Our results demonstrate that both termite guts and termite galleries harbor unique bacterial communities.IMPORTANCE As is the case for all ecosystem engineers, termites impact their habitat by their activities, potentially affecting bacterial communities. Here, we studied three wood-feeding termite species and found that they influence the composition of the bacterial communities in their surrounding environment. Termite activities have positive effects on Rhizobiales and Actinobacteria abundance and negative effects on the abundance of several ubiquitous genera, such as Bacillus, Clostridium, Corynebacterium, and Staphylococcus Our results demonstrate that termite galleries harbor unique bacterial communities.
Keywords: Isoptera; mikrobiota; Biodiversity; symbiosis; RNA ribozomální 16S; druhová specificita; biodiverzita; Coptotermes; Bacteria; ectosymbionts; Animals; Microbiota; Heterotermes; zvířata; Species Specificity; RNA, Ribosomal, 16S; Nasutitermes